The Impact of the German Strategy for Containment of Coronavirus SARS-CoV-2 on Training Characteristics, Physical Activity and Sleep of Highly Trained Kayakers and Canoeists: A Retrospective Observational Study - Zinner, Christoph; Matzka, Manuel; Leppich, Robert; Kounev, Samuel; Holmberg, Hans-Christer; Sperlich, Billy (Frontiers in Sports and Active Living, 2020)
Aim: To characterize the impact of the German strategy for containment of Coronavirus SARS-CoV-2 (social distancing and lockdown) on the training, other habitual physical activity, sleep in highly trained kayakers and canoeists. Method: During the four weeks immediately prior to and following the beginning of the German government’s strategy for containment of Coronavirus SARS-CoV-2 on March 23, 2020, 14 highly trained athletes (VO2peak: 3162±774 ml/min; 500-m best time: 117.9±7.9 s) wore a multi-sensor smartwatch to allow continuous assessment of heart rate, physical activity, and sleep duration. Result: In comparison to before lockdown, overall weekly training time and the average length of each session of training during the lockdown decreased by 27.6% (P=0.02; d=0.91) and 15.4% (P=0.36; d=0.36), respectively. At the same time, the numbers of sessions involving specific (i.e., canoeing and kayaking) and non-specific (i.e., running, cycling) training were unchanged (P=0.36-0.37; d=0.34-0.35). The numbers of sessions involving strength (+17.4%; P=0.03; d=0.89) or other types of training (+16.7%; P=0.06; d=0.75) were greater during than before lockdown, with 2.8-17.5% more training time involving a heart rate <60%, 82-88%, 89-93% or 94-100% of individual peak heart rate (HRpeak) (P=0.03-0.86; d=0.07-1.38) and 4.3-18.7% less time with a heart rate of 60-72% or 73-83% HRpeak (P=<0.001-0.0.26; d=0.44-2.24). The daily duration of sleep was approximately 30 min (6.7%) longer during than before lockdown (P<0.001; d=1.53) and overall time spent lying down 17% greater (P<0.001; d=2.26); whereas sitting time (-9.4%; P=0.003; d=1.23) and the duration of light (15 min; -7.3%; P=0.04; d=0.83) and moderate (-18.6%; P=0.01; d=1.00) physical activity other than training (-9.4%; P=0.22; d=0.00) were all lower during lockdown. Conclusion: The present data revealed that following the German lockdown for containment of the Coronavirus SARS-CoV-2, highly trained kayakers and canoeists spent less overall time training each week (-27.6%), with, on average, shorter training sessions (-15.1%), and less light-to-moderate physical activity outside of training. Moreover, they performed more strength training sessions per week, and all engaged in more training at intensities >82% and <60% of HRpeak, as well as longer periods lying down and sleeping during than prior to the lockdown.